Persepsi Mahasiswa Pada Isu Penggunaan Ghibli Art AI di Media Sosial Sebagai Mata Pencaharian - Dearni Anjelina Panjaitan; Meyshinta Aulia; Yeni Juliana; Moh. Afdol; Rio Kurniawan (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
Studio Ghibli is widely known for its distinctive visual style and aesthetic value, making it a source of inspiration for many digital artists. In the era of technological advancement, a new phenomenon has emerged in the form of Ghibli-style artworks produced by artificial intelligence (AI). Without manual drawing skills, anyone can now create Ghibli-style illustrations simply by inputting text or reference images. In Indonesia, this trend is growing rapidly and is even used as a livelihood by some students. However, the commercial use of Ghibli's visual style without permission raises ethical and legal issues, considering that Studio Ghibli has never approved the practice. This study aims to analyze how mass media influences students' perceptions of the use of Ghibli-style AI art as a means of earning income. The main focus lies on how the media frames the issue, as well as how students understand the legitimacy, ethics, and economic value of the AI works. The approach used is descriptive qualitative with data collection techniques in the form of in-depth interviews, digital observation, and literature study. The results show that mass media plays an important role in shaping students' opinions, especially in legitimizing or creating doubts about this practice. Exposure to media that support technological advancement tends to make students more accepting of the use of AI art as an economic opportunity. Conversely, media that highlight ethical and copyright issues tend to trigger critical attitudes towards the practice. This research emphasizes the importance of media literacy and digital ethics in dealing with the dynamics of today's art technology. This finding confirms that students are not passive in receiving information from mass media; they sort and judge based on personal values, social context, and economic needs. Thus, mass media not only functions as a source of information, but also as an agent of shaping perceptions and ethical considerations in the era of creative technology.